A Sociological Imagination: The Neglected Concept in Transformation Theory - Fleming, Ted (Adult Education Critical Issues, 2024)
Malcolm Knowles visited Teachers College as I commenced studying there in 1978. But Paulo Freire’s Pedagogy of the Oppressed opened the possibility that adult education could be radical and transformative. In the same year Jack Mezirow (1978) published his theory of perspective transformation. Andragogy was useful but a paradigm shift in the field of adult education had occurred and through multiple iterations over the following decades we are the inheritors of these exciting developments. Mezirow borrowed from Jürgen Habermas whose theory of communicative action he creatively integrated with the theory of transformative learning (TL). Adult education, that traditionally linked itself with the project of democracy, had a new critical theory inspired understanding of adult learning that works towards democracy. It is this connection that makes TL important in a world facing multiple (connected) crises – climate change, radicalizations, the rise of the far right and wars.